Sistem Pendukung Keputusan Penilaian Karyawan Terbaik Menggunakan Metode Multi Attribute Utility Theory - Kosasih, Indra; P Kesuma, Dorie (Universitas Multi Data Palembang, 2024)
PT Sumber Ban Perkasa is a car tire distributor that focuses on selling tires, spare parts and car repairs. In determining the best employees at PT Sumber Ban Perkasa there is no clear weighting and there is not a good enough standardized assessment. PT Sumber Ban Perkasa needs a system that suits its needs and can provide objective and transparent assessment results. The system development methodology used is the Waterfall methodology which has 5 phases, namely requirements analysis, system design, implementation & unit testing, system testing, and maintenance. In this research, the Multi Attribute Utility Theory (MAUT) method is used as a decision support system method. In designing applications at PT Sumber Ban Perkasa using the PHP and MySQL programming languages which are used as database storage. By creating the best employee assessment decision support system, the result is that it can overcome obstacles in employee assessment, increase the objectivity of the assessment, and make a positive contribution to efficiency and transparency at PT Sumber Ban Perkasa.